Estomatologic manifestations in HIV/AIDS patients - Garibay Rodríguez, Lorena Elvira (2007)
The study was carried out at Hospital Nacional Guillermo Almenara Irigoyen, on 128 patients infected by the human inmunodefense virus. The aim of the investigation was to study the frecuency, and location of oral lesions, in relation with age and sex, also to establish the relationship between CD4 cells counts with oral lesions detected. The sample were selected in a probabilistic way; the data was recorded in a special designed format. 74 subjects of the sample were male and 57 female. Oral lesions were found in 57,8% and 43,8% of the infected patients were between 26 and 35 ages. Pseudomembranous candidiasis was the most common lesion detected in 21,9% of patients (tongue, soft palate and cheeks), ulcers 14,1% (cheek, tongue and lips), erytematous candidiasis in 10,1% (soft palate), angular queilitis in 10,1% and oral hairy leukoplakia in 7%. Pseudomembranous candidiasis and oral hairy leukoplakia are clinical indicators of immunologic deterioration ( CD4 200 ce/mm3).